2020
DOI: 10.1108/ijbpa-08-2020-0072
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of spatial configuration management on social distancing of recreational clubhouse for COVID-19 in Penang, Malaysia

Abstract: PurposeSince the appearance of COVID-19 social distancing and staying home have been recommended repeatedly by the governments for disease prevention. As the challenge continues to remain the current study seeks to examine the factors affecting social distancing through space planning and management. More specifically the current study aims to examine the appropriateness of the spatial organization and space configuration of a clubhouse with a linear plan layout in the mitigation of the spread of infections du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The other notable point can be related to the substantial efficacy of COVID-19 on reducing tendencies for the establishment of social interactions among visitors. This issue may lead the visitors to acquire a sense of social isolation, which based on previous studies, negatively affects their mental well-being [94] . In relation to the impact of COVID-19 on the wayfinding procedure of visitors, the majority of participants in the interview corroborated their sense of confusion throughout the process of identifying their destinations.…”
Section: Discussionmentioning
confidence: 99%
“…The other notable point can be related to the substantial efficacy of COVID-19 on reducing tendencies for the establishment of social interactions among visitors. This issue may lead the visitors to acquire a sense of social isolation, which based on previous studies, negatively affects their mental well-being [94] . In relation to the impact of COVID-19 on the wayfinding procedure of visitors, the majority of participants in the interview corroborated their sense of confusion throughout the process of identifying their destinations.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially effective interventions for the building include: (1) Spatial measures need to be implemented according to on-site ventilation conditions, population density, occupant behavior and spatial conditions. For example, dividing the office area into smaller units to avoid excessive crossing of routes and large-scale aerosol diffusion could be an effective measure under normal- or high- efficiency ventilation conditions [ 80 , 94 ]. However, with poor ventilation, aerosols in cubicles cannot be diluted by clean air and are more likely to accumulate in the room, leading to high infection risk of occupants.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Integrated and intelligible structures have been shown to enhance movement volume in more accessible and central places, as well as the number and variety of microbes [ 79 ]. Abdul et al [ 80 ] quantified the impact of spatial permeability and wayfinding levels ( Table 6 ) on COVID-19 transmission and social distancing using an analysis method of space syntax, and the results showed that clear and direct spatial organization was associated with more effective social distancing. Compared with the grid plan, the linear-plan layout is considered to reduce the risk of user crossing due to its convenience of pathfinding.…”
Section: The Role Of Spatial Factors On Sars-cov-2 Transmissionmentioning
confidence: 99%
“…Thus, many countries that have experienced increasingly severe outbreaks have implemented population-level physical-distancing measures and movement restrictions, such as business closures, community lockdowns, and the cancellation of large-scale public gatherings, which have slowed the transmission of SARS-CoV-2 [4] . However, the effects of spatial configurations on physical distancing-based attempts to prevent SARS-CoV-2 transmission remain unclear [5] , [6] . Specifically, despite the consensus that physical distance should be maintained between people [6] , there are few data and even less agreement on what kinds of spatial layouts are needed and what proportion of physical isolation is required on a micro-scale.…”
Section: Introductionmentioning
confidence: 99%